Radical Pie

Algebra Level 1

( 3 3.14 ) 2 + ( 3.14 3 ) 2 \large \sqrt{ ( \color{#20A900} 3 - \color{#3D99F6} {3.14}) ^2 } + \sqrt{ ( \color{#3D99F6} {3.14} - \color{#20A900} 3 ) ^ 2 }

Evaluate the above expression.

0.45 0.28 0.6 0.3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

7 solutions

Pranjal Jain
Feb 19, 2015

x 2 = x \sqrt{x^2}=|x|

3 3.14 + 3.14 3 = 0.14 + 0.14 = 0.28 |3-3.14|+|3.14-3|=0.14+0.14=0.28

( 3 3.14 ) 2 + ( 3.14 3 ) 2 \sqrt{ ( 3 - 3.14 ) ^2 } + \sqrt{ ( 3.14 - 3 ) ^2 } = ( 3 - 3.14 ) + ( 3.14 - 3 ) = 3 - 3.14 + 3.14 - 3 = 0

শিবু মল্লিক - 6 years, 3 months ago

Log in to reply

No, ( 3 3.14 ) 2 3 3.14. \sqrt{(3 - 3.14)^2} \neq 3 - 3.14. The square root does not "cancel" the square, since square root returns only positive values. In fact, ( 3 3.14 ) 2 = 3 3.14 = 0.14 , \sqrt{(3 - 3.14)^2} = |3 - 3.14| = 0.14, not 0.14. -0.14.

Caleb Townsend - 6 years, 3 months ago
Victor Loh
Feb 26, 2015

( 3 3.14 ) 2 + ( 3.14 3 ) \sqrt{(3-3.14)^2}+\sqrt{(3.14-3)} = ( 0.14 ) 2 + ( 0.14 ) 2 =\sqrt{(-0.14)^2}+\sqrt{(0.14)^2} = ( 0.14 ) 2 + ( 0.14 ) 2 =\sqrt{(0.14)^2}+\sqrt{(0.14)^2} = 0.14 + 0.14 =0.14+0.14 = 0.28 =\boxed{0.28}

cant we just cancel the roots

abhishek alva - 4 years, 9 months ago
Ramez Hindi
Feb 21, 2015

since 3 3.14 3 \leq3.14 then 3 3.14 0 3-3.14\leq0 thus 3.14 3 0 3.14-3\geq0 Now we have ( 3 3.14 ) 2 + ( 3.14 3 ) 2 . \sqrt{ ( 3 - 3.14) ^2 } + \sqrt{ ( 3.14 - 3 ) ^ 2 }. and we know that x 2 = x \sqrt{x^2}=|x| thus 3 3.14 + 3.14 3 = ( 3 3.14 ) + ( 3.14 3 ) = 3.14 3 + 3.14 3 |3-3.14|+|3.14-3|=-(3-3.14)+(3.14-3)=3.14-3+3.14-3 = 0.28 =0.28

Gamal Sultan
Feb 20, 2015

(3.14 - 3)^2 = (3 - 3.14)^2 = (0.14)^2

So

square root of [(3 - 3.14)^2] + square root of [( 3.14 - 3)^2] = (0.14) + (0.14) = 0.28

Sadasiva Panicker
Oct 22, 2015

(3 - 3.14) + 3.14 - 3) = -.14 + .14 So root of (3 - 3.14)^2 + root of (3.14 - 3)^2 = root of (-.14)^2 + root of(.14)^2 = .14+.14 = .28

Guyshirjit Singh
Mar 8, 2015

± (3-3.14) ± (3.14-3)

If we consider both signs as '+' or '-', then we get zero.

If we consider opposite signs then we get 0.28 as the solution.

Both solutions are possible but one matching with the option is considered.

Just to support ±;

√16 = +4 and -4, or we can say ±4

Gagan Raj
Feb 17, 2015

The first part of the sum = 0.14 = The second part of the sum.

Thus the answer is 0.14 + 0.14 = 0.28

should be 0 3-3.14+3.14-3=0 squa re root of square of a number is simply the number

Arshad Vains - 6 years, 3 months ago

Log in to reply

no sir square root of a negative number is not the number itself sir...........it is a complex number............that is why we first subtract then square it up so that it becomes +ve and then take the root of it...........then the number is "ITSELF'......not directly. Or else we can take the square root of the square of a number as the absolute value of the number i.e. the Modulus of the number irrespective of the sign of the number. Then the number is "ITSELF".

Gagan Raj - 6 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...